The impact of cross-curricular teachers’ level of assessment literacy in the EFL classroom on elementary school students’ development of Output language skills in rural contexts: a case study - Arango Velasquez , Juan Andrés; Ceballos Borrero, Camilo; Diaz Berrio, Jennifer (Universidad Católica Luis Amigó, 2023)
This research highlights the challenges faced while teaching English as a foreign language (EFL) in Colombian public elementary schools, despite the government's efforts to promote bilingualism. Homeroom teachers, who frequently lack formal academic education for teaching English, are primarily responsible for teaching English. This lack of preparation is evident in their limited knowledge regarding assessment and its appropriate application, resulting in the repetitive use of ineffective assessment tools and activities. Consequently, students in rural contexts exhibit a lack of production and receptive language skills, leading to demotivation and hindered development of communicative competences. The lack of assessment literacy among cross-curricular teachers has direct consequences for students' development of communicative competences. In rural contexts, limitations exist not only in providing input, but also in facilitating output language skills. Teachers need to be skilled in various aspects of assessment, such as selecting appropriate methods, interpreting results, and communicating outcomes to improve teaching practices. The research aims to explore the impact of cross-curricular teachers' assessment literacy on students' output language skills in the EFL classroom in rural contexts. In conclusion, the research highlights the challenges faced by cross-curricular teachers in developing students' communicative competences in rural elementary schools. The lack of assessment knowledge, English proficiency, and available training contribute to the ineffective teaching and assessment practices observed. The study emphasizes the importance of proper application of assessment, overcoming teachers' fears regarding English proficiency, and focusing on meaningful language learning experiences. Improving teachers' assessment literacy and understanding of how children learn languages are essential for enhancing English language instruction in elementary schools.
Keywords: Assessment; Assessment literacy; Cross-curricular teachers; Output; a